2016
DOI: 10.1099/jmm.0.000286
|View full text |Cite
|
Sign up to set email alerts
|

Major components of orange oil inhibit Staphylococcus aureus growth and biofilm formation, and alter its virulence factors

Abstract: Bovine mastitis is a costly disease in the dairy industry and does not always respond to antibiotic treatment. The major components of terpeneless, cold-pressed Valencia orange oil -citral, linalool, decanal and valencene -were examined as potential alternative treatments for Staphylococcus aureus-associated mastitis. The minimum inhibitory concentration (MIC) of all four components against S. aureus was determined after incubation for 24 h. Growth inhibition assays were performed for all effective components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 41 publications
0
16
1
Order By: Relevance
“…In the current study, we found significant increases in specific constitutes of the essential oil of plants subjected to salinity and SA such as linalool, camphor, borneol, and caryophyllene oxide. For example, Federman et al ( 2016 ) reported that the major oil constitute of the orange was the linalool responsible for inhibiting growth and biofilm formation in S. aureus .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we found significant increases in specific constitutes of the essential oil of plants subjected to salinity and SA such as linalool, camphor, borneol, and caryophyllene oxide. For example, Federman et al ( 2016 ) reported that the major oil constitute of the orange was the linalool responsible for inhibiting growth and biofilm formation in S. aureus .…”
Section: Discussionmentioning
confidence: 99%
“…aureus Inhibits Staph. aureus internalization by inhibiting NF-κB activation Citral and linalool [101] MAC-T Staph. aureus Inhibits Staph.…”
Section: Plant-derived Compoundsmentioning
confidence: 99%
“…It was found out that major components of CDO, citral, and linalool are responsible for inhibition, owing to their abilities to alter the expression of Staph. aureus virulence genes [101]. On the contrary, CDO has also been reported to not impair the function of polymorphonuclear leukocytes, which play an important role in immune response against mastitis, at the same time inhibiting bacterial growth [102].…”
Section: Plant-derived Compoundsmentioning
confidence: 99%
“…Various studies have shown the antimicrobial activity of components of essential oils, such as citral, on strains of S. aureus , inhibiting biofilm formation or altering virulence factors. It is known that essential oils and major components can act to deregulate virulence genes, in addition to antibacterial, antifungal, analgesic, antispasmodic, and antiparasitic activities, in addition to fighting nerve disorders 15 , 17 , 18 . Despite the antibacterial properties of this oil against gram-positive and gram-negative bacteria, its prolonged use has not shown resistance 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%